The Willingness to Pay-Willingness to Accept Gap, the "Endowment Effect," Subject Misconceptions, and Experimental Procedures for Eliciting Valuations - Plott, Charles R.; Zeiler, Kathryn (The American economic review, 2005)
We conduct experiments to explore the possibility that subject misconceptions, as opposed to a particular theory of preferences referred to as the "endowment effect," account for reported gaps between willingness to pay ("WTP") and willingness to accept ("WTA"). The literature reveals two important facts. First, there is no consensus regarding the nature or robustness of WTP-WTA gaps. Second, while experimenters are careful to control for subject misconceptions, there is no consensus about the fundamental properties of misconceptions or how to avoid them. Instead, by implementing different types of experimental controls, experimenters have revealed notions of how misconceptions arise. Experimenters have applied these controls separately or in different combinations. Such controls include ensuring subject anonymity, using incentive-compatible elicitation mechanisms, and providing subjects with practice and training on the elicitation mechanism before employing it to measure valuations. The pattern of results reported in the literature suggests that the widely differing reports of WTP-WTA gaps could be due to an incomplete science regarding subject misconceptions. We implement a "revealed theory" methodology to compensate for the lack of a theory of misconceptions. Theories implicit in experimental procedures found in the literature are at the heart of our experimental design. Thus, our approach to addressing subject misconceptions reflects an attempt to control simultaneously for all dimensions of concern over possible subject misconceptions found in the literature. To this end, our procedures modify the Becker-DeGroot-Marschak mechanism used in previous studies to elicit values. In addition, our procedures supplement commonly used procedures by providing extensive training on the elicitation mechanism before subjects provide WTP and WTA responses. Experiments were conducted using both lotteries and mugs, goods frequently used in endowment effect experiments. Using the modified procedures, we observe no gap between WTA and WTP. Therefore, our results call into question the interpretation of observed gaps as evidence of loss aversion or prospect theory. Further evidence is required before convincing interpretations of observed gaps can be advanced.